Species Composition and Distribution of Methicillin-Resistant, Inducible Clindamycin-Resistant, and Multidrug-Resistant Staphylococci Causing Clinical Infections in Benin City, Nigeria - Ibadin, Ephraim; Omoregie, Richard; Eriamiatoe, Richard; Idemudia, Lawrence; Eghiomon, Angela; Onuoha, Peter; Dedekuma, Eghonghon; Anogie, Nana; Omoike-Okosun, Omoye; Igunma, Jeremiah; Ehondor, Ogie; Ібадін, Ефраїм; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Researchers are still interested in the genus Staphylococcus because of its virulence and antimicrobial resistance (AMR) in different strains, which have increased infection-related morbidity and mortality. This study aimed to determine the species and distribution of methicillin-resistant, inducible clindamycin-resistant, and multidrug- resistant (MDR) staphylococci causing clinical infections in Benin City, Nigeria. Methods. Three hundred and thirty-five staphylococcal isolates were recovered from clinical specimens over one year. These isolates were identified, and antimicrobial susceptibility tests including methicillin resistance (MR), inducible clindamycin resistance (iMLSB), and vancomycin resistance were carried out using the VITEK-2 Compact System. Result. The most common species causing infections were S. aureus and S. haemolyticus. Overall, 71.2% and 89.5% of S. aureus and Coagulase-negative staphylococci (CoNS), respectively, were methicillin-resistant. Only 19.1% of the isolates were tested positive for iMLSB, with S. saprophyticus having the highest prevalence (29.4%), followed by S. aureus with 16%. A low prevalence of vancomycin resistance was observed (1.5%) as only S aureus (2.4%) and S. haemolyticus (1.7%) showed resistance. Majority of isolates were MDR (72.5%) while S. haemolyticus had the highest prevalence (94.1%). Compared with methicillin-sensitive staphylococci, methicillin-resistant staphylococci were significantly more likely to be MDR (17.2% vs 83.3%, OR=23.489 95%CI=11.093, 49.740, p < 0.0001).  Concerning susceptibility profile, S. haemolyticus was the least susceptible to the tested antibacterial agents. The most active antibacterial agents against Staphylococcus spp were tigecycline (99.7), linezolid (99.1%), nitrofurantoin (98.8%), and daptomycin (96.4%), while the least active were trimethoprim-sulfamethoxazole (31.3%) and the quinolones ciprofloxacin (32.2%) and levofloxacin (33.1%). Conclusions. A high prevalence of MR-staphylococci that were MDR was observed in this study. There is a need to enact and implement antibiotic stewardship guidelines to reverse the rising tide of AMR.